Practice and Exploration of Happy Rivers and Lakes on Plateau: Case Study on Zhongqu River of Tibet - YAO Shi-ming, LUO Ping-an (长江科学院院报)
The construction of happy rivers and lakes is a significant initiative to expedite ecological civilization construction and a crucial task for the river-lake chief system at present and in the future. Taking the construction of a happy river and lake project in Zhongqu, Tibet as a case study, we outline 15 key tasks of the Zhongqu project from three aspects: river system governance, improvement of river management capacity, and support for the development of the watershed region. Subsequently, in comparison with the work plan for evaluating the effectiveness of happy-river-and-lake construction, we analyze the effectiveness of the Zhongqu project from seven perspectives: safety, ecology, livability, intelligence, culture, development, and public satisfaction. Given the unique geographical location, climatic conditions, topography, ecological environment, and cultural customs in the Zhongqu watershed, we discuss the challenges and propose corresponding solutions and suggestions. The pilot exploration of constructing happy-river-and-lake project for the Zhongqu River offers a theoretical foundation and technical reference for similar projects on the plateau.